Pre-Operative, High-IL-6 Blood Level is a Risk Factor of Post-Operative Delirium Onset in Old Patients - Capri, Miriam; Yani, Stella Lukas; Chattat, Rabih; Fortuna, Daniela; Bucci, Laura; Lanzarini, Catia; Morsiani, Cristina; Catena, Fausto; Ansaloni, Luca; Adversi, Marco; Melotti, Maria Rita; Di Nino, Gianfranco; et al. (Frontiers in Endocrinology, 2014)
Background: Postoperative delirium (POD) is a common complication in elderly patients undergoing surgery, but the underpinning causes are not clear. We hypothesized that inflammaging, the subclinical low and chronic grade inflammation characteristic of old people, can contribute to POD onset. Accordingly, we investigated the association of preoperative and circulating cytokines in elderly patients (>65 yrs), admitted for elective and emergence surgery. Methods: This is secondary analysis of a sub-cohort of patients belonging to a previous large case-control study, where 351 patients were clinically and cognitively thoroughly characterized, together with the assessment of POD (47 patients) by Confusion Assessment Method (CAM) and Delirium Rating Scale (DRS). 74 preoperative plasma samples were selected from a larger bio-bank and they included 37 subjects with POD and 37 without POD. Inflammaging related cytokines, i.e. IL-1 β, IL-2, IL-6, IL-8, IL-10 and TNF-α were assayed by ELISA in pre-operative blood samples; univariate and multivariable analyses have been applied to identify cytokines independently associated to POD. Associations of cytokine levels with functional status, cognitive decline, intra-hospital mortality and comorbidity were also analyzed independently of POD onset. Results:. High IL-6 and low IL-2 levels were significantly associated with POD. After adjustment for potential confounders in multivariate analysis, high level of preoperative IL-6 was confirmed to be significantly associated with risk of POD onset.. High level of IL-6 was also associated with several baseline features (including poor functional status, cognitive impairment, emergency admission and higher comorbidity burden) and intra-hospital mortality. Conclusions: Preoperative, high plasma level of IL-6 ( ≥ 9 pg/mL) was significantly associated with POD onset. We propose IL-6 as an additional risk factor of POD onset together with the previously identified factors. Discovery of all risk